Influences of Hybrid Cooling Mechanism through PV System under Solar Simulator Testing - Y.M. Irwan; A.R. Amelia; M. Irwanto; W.Z. Leow; Z. Syafiqah; I. Safwati (International Journal of Advances in Applied Sciences, 2017)
An increasing efficiency of the solar system can be improved by using hybrid cooling mechanism. This paper presents the impact of hybrid cooling mechanism on PV panel under indoor testing with varying solar intensity. Thus, the fabrication of a solar simulator for indoor testing reacts as the space solar radiation is described. The performance of PV panel which attached to a hybrid cooling mechanism compared with PV panel without cooling mechanism under variation of average solar radiation. Experimental tests were carried out for various average solar radiations by varying the number of lamps and/or the lamp-to-area distance. Without altering the spectral distribution, the characteristic of current-voltage of PV panel was analysed under average solar radiation which varied from 202 W/m2 to 1003 W/m2. As the result, the PV panel with hybrid cooling system explored to generate more power output with decreasing in PV panel temperature. About 15.79 % increment of power output generated by PV panel with cooling at maximum average solar radiation. Furthermore, the PV panel temperature also can be decreased about 10.28 % respectively. The combination of DC fan and water pump as cooling mechanism plays an important role in generating efficient power output from PV panel.